Pengaruh Strategi Pembelajaran Problem Based Learning (PBL) Dan Group Investigation (GI) Terhadap Keterampilan Proses Sains Di MAN Kabanjahe - Ginting, Iskandar Dinata; Djulia, Ely; Gultom, Tumiur (Jurnal Pendidikan Biologi, 2017)
This study aims to determine the effect of learning strategies on the skills of the science process. The research method used quasi experiment with research sample of 3 classes determined randomly with cluster random sampling technique. Class A is taught by Problem Based Learning strategy, class B with Group Investigation and Class C (Control) learning strategy using Conventional learning strategy. The research instrument uses a science skill test in the form of a description of the observation sheet. Data analysis techniques with Covariate Analysis (ANACOVA) at significant level Î± = 0.05 with the help of SPSS 24. The results showed there is a significant influence of learning strategy on science process skills (F = 9,229; P = 0,000). As a follow-up of the results of this study is expected to teachers to be able to implement Problem Based Learning (PBL) strategy on Ecology material in an effort to improve the skills of science process.